Rumanía en el contexto geopolítico del Mar Negro - Marcu, Silvia (Geographicalia, 2015)
The article sets out to approach which is the present position that has Rumanía, European, Balkan, Carpathians, Danube, and Pontiac's country, in the geopolitical region of the Black Sea, like member of the Atlantic Alliance and on the eve of its entrance in the UE.The first part display the present frame of the geopolitical region of the BlackSea, so that, next the Rumanían geopolitical dimensions, their new strategy and the priorities of performance in the zone are analyzed, emphasizing the American influence and the recent proposal of the country to constitute strategic partnership Washington-London-Bucharest. The third part analyzes the Rumanian implications in the tensions of the countries of the river basin of the Black Sea, exemplifying the cases of Transdniester, the island of the Serpents and the construction on the part of the Ukraine, of the Bastroe arm in the delta of the Danube. Finally, the gravitation of Rumanía in the geopolitical system of the Black Sea of century XXI is analyzed.
Keywords: Romania; geopolitics; tlie Ulack Sea; strategy; region